Reliability and intermetallic characterization of palladium-clad copper wire bond on aluminum pad under mixed stresses - Daep, Ryan Cedric O.
Gold wire bonding is the most utilized process in microelectronic interconnects. But, the price of gold is constantly increasing. For this reason, several studies have considered copper as a potential low-cost alternative to gold because of its higher electrical conductivity and mechanical properties. Copper readily oxidizes when heated, thus creating issues concerning its reliability. In recent studies, Palladium was added to copper wire as a surface coating that would prevent oxidation. The acceptance of this new material in the industry requires better understanding of its reliability under mixed stresses. In this study, palladium-clad copper wire bonds on aluminum bond pads were investigated together with gold wires. Lead frame chip-scale package (LFCSP) samples with palladium-clad copper and samples with gold wires were baked at 150°C, 200°C, and 275°C for 500 and 1000 hours. After baking, the electrically functional samples, determined using a curve tracer, were subjected to pressure cooker test (PCT), which has a chamber pressure of 2 atm, temperature of 121°C, and 100% relative humidity. SEM/EDX analysis showed no signs of oxidation up to 200°, and all samples were still electrically functional at this temperature. Ball bond strength increased with increasing IMC thickness. The overall performance of copper-palladium wire was comparable to gold wire up to 200°C. Copper wires were oxidized at 275°C, which could be associated with the observed physical deterioration of the molding compound and diffusion of palladium into the wire. Gold wires also showed signs of damage at 275°C. Cu-Al and Au-Al IMC growth profiles followed the parabolic rate law, indicating that the formation was diffusion-controlled. The thicker Au-Al IMC indicates that it is more sensitive to temperature compared to the Cu-Al IMC.